REKONSILIASI SYARIAT DAN TASAWUF DALAM KONSEP AL-GHAZALI - Irwan Supriadin J (STIT Sunan Giri Bima, 2022)
This paper is a literature study using a qualitative descriptive approach that aims to describe al-Ghazali's ideas in reconciling between Shari'a and Sufism. This study found that although al-Ghazali believed in Rasa (Dzawq), it did not cause him to doubt reason as a tool in reaching the truth. Intellect is required to analyze and understand religious matters, while the concept of ma'rifat which is characteristic of al-Ghazali is a development of concepts that have existed before. In his efforts to reconcile Shari'ah and Sufism, al-Ghazali is able to provide explanation of the close relationship between shari'ah and Sufism, but behind that, al-Ghazali has not been fully able to place the two on the same level . This can be seen from the stratification – lay and concerned – for Muslims who do good deeds, so that they unconsciously fall back into the tendency of Sufi superiority.